Sex determination in Japanese quails (Coturnix japonica) based on head morphometry variation among age - DEVIA YOANITA KURNIAWATI; YULIANNA PUSPITASARI; ADITYA YUDHANA; AMUNG LOGAM SAPUTRO; YENI DHAMAYANTI; AGUS PURNOMO; MUHAMMET BAYRAM; MUHAMMAD THOHAWI ELZIYAD PURNAMA (Biodiversitas Journal of Biological Diversity, 2024)
Abstract. Kurniawati DY, Puspitasari Y, Yudhana A, Saputro AL, Dhamayanti Y, Purnomo A, Bayram M, Purnama MTE. 2024. Sex determination in Japanese quails (Coturnix japonica) based on head morphometry variation among age. Biodiversitas 25: 2740-2748. Sex determining of the Japanese quail (Coturnix japonica) is very crucial to increase the economic value during the rearing period. This study aimed to investigate the potential age at which Japanese quail sex may be recognized using head morphometry assessment. Forty-three quail in all were reared at random and labeled numbers until they turned fifty days old. Without considering sex into account, measurements of each quail's head morphometry and body weight were performed on days 10, 20, 30, 40, and 50. Skull Length (SL), Cranial Length (CL), Viscerocranium Length (VL), Maximum Width of Neurocranium (MWN), Beak Width (BW), Zygomaticus Width (ZW), Skull Height (SH), and Bill Depth (BD) were the characteristics that were assessed. To categorize data according to age and sex, quail was verified on day 50 using observations of the abdominal cavity. As a result, initially, on day 20, considerable morphometric variations between male and female quail were observed for the morphometric parameters MWN, BW, ZW, and BD. It was reported that the male quail's MWN (p<0.001), BW (p<0.001), ZW (p<0.001), and BD (p<0.001) parameters were significantly wider than those of the females. A positive correlation was reported for SL, CL, VL, MWN, BW, ZW, SH, and BD parameters, despite the lack of significant differences in body weight. In conclusion, quail sex can be determined using head morphometry as early as 20 days of the rearing period.